2015
DOI: 10.1080/09658211.2015.1013557
|View full text |Cite
|
Sign up to set email alerts
|

Serial-position effects on a free-recall task in bilinguals

Abstract: In this study, we examined mechanisms that underlie free-recall performance in bilinguals’ first language (L1) and second language (L2) through the prism of serial-position effects. On free-recall tasks, a typical pattern of performance follows a U-shaped serial-position curve, where items from the beginning of the list (the primacy effect) and items from the end of the list (the recency effect) are recalled with higher accuracy than items from the middle of the list. The present study contrasted serial-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…In SLR, EBs recalled more information than LBs. This aligns with previous studies showing that AoA is associated with information encoding and retrieval in cued word (Yoo and Kaushanskaya, 2016;Macmillan et al, 2021) and picture (Volkovyskaya et al, 2017) extends these findings, suggesting that AoA can also modulate information recall in the face of ecological textual materials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In SLR, EBs recalled more information than LBs. This aligns with previous studies showing that AoA is associated with information encoding and retrieval in cued word (Yoo and Kaushanskaya, 2016;Macmillan et al, 2021) and picture (Volkovyskaya et al, 2017) extends these findings, suggesting that AoA can also modulate information recall in the face of ecological textual materials.…”
Section: Discussionsupporting
confidence: 92%
“…First, our sample size was moderate. Although it was supported by power estimation results and it proved similar to or larger than those of other relevant studies in the field (Sabourin et al, 2014;Giezen et al, 2015;Yoo and Kaushanskaya, 2016), future research should replicate our experiment with more participants. Second, the current study used only two tasks, with brief texts allowing for no interaction.…”
Section: Limitations and Avenues For Further Researchsupporting
confidence: 85%
See 1 more Smart Citation
“…We observed overall serial order effects in the SRTs in German and Russian: in contrast to Alloway and Gathercole (2005), we found that the medial position was especially vulnerable to omissions in both languages, showing a higher number than the final or initial position. This finding confirms a great body of literature from cognitive psychology on primacy and recency effects in other types of recall tasks (e.g., Yoo & Kaushanskaya, 2016;Brown et al, 2017;Hitch et al, 2020), as well as some early studies on typical child language acquisition, such as Gleitman et al (1984). Additionally, in German, those children whose identical repetition scores are better are more likely to maintain the initial and final positions and omit only in the medial position, while children with low identical repetition scores are more likely to omit items in all three positions.…”
Section: Discussionsupporting
confidence: 88%
“…If listening to voice disordered speech is a sufficiently adverse listening situation, then memory might be hindered, but effects might not manifest evenly across all of the words in a list. For example, the typical u-shaped serial-position curve of word recall, in which there is a primacy effect (i.e., the beginning of the list is remembered better than the middle) and a recency effect (i.e., the end of the list is remembered better than the middle), can be altered by adverse listening situations, such as background noise [ 10 , 11 ] and second language processing [ 12 ]. Specifically, evidence indicates that, in some cases, adverse listening situations can reduce the primacy effect and/or recency effect.…”
Section: Introductionmentioning
confidence: 99%